The resources of the school museum in regular and extracurricular activities - Kaltsanova E. V., Grigogreva R. L. (University as a factor of Modernization of Russia: History and Prospects (to the 55th anniversary of the I.N. Ulyanov ChSU), 2024)
this article examines the possibilities of using the resources of the school museum «Memory Road» of Secondary School No. 64 in Cheboksary, Chuvash Republic, in patriotic education in the classroom and in extracurricular activities. These resources provide an opportunity for the initial study of the events of the history of the Great Patriotic War and to visualize military events using information technologies that increase the educational motivation of a modern student.
Keywords: Великая Отечественная война; внеурочная деятельность; extracurricular activities; школьный музей; музейная педагогика; культурно-историческое наследие; The Great Patriotic War; museum pedagogy; school museum; cultural and historical heritage